THE VERBAL POLITENESS OF INTERPERSONAL UTTERANCES RESULTED FROM BACK-TRANSLATING INDONESIAN TEXTS INTO ENGLISH - Mujiyanto, Yan (Indonesian Journal of Applied Linguistics, 2017)
Verbal politeness can be considered from the perspectives of linguistic features, participants’ socio-cultural background and their membership within a speech community. It can also be viewed from the ways to which it applies in interpersonal utterances, be they source or target ones. It may also be taken into account from its users’ perception as well their maintenance in real communication. This paper aimed to explore (1) the degree of the verbal politeness contained in English interpersonal utterances, (2) the correlation of politeness degrees between the English utterances as the source texts and their back-translations, (3) the speakers’ perception of the politeness degrees contained in the two sets of utterances, and (4) the ways of maintaining them. The object of this study was verbal (im)-politeness contained in English interpersonal utterances which were back-rendered from translated texts in Indonesian. In order to elicit the type of utterances from the subject of this study, the Indonesian utterances were exposed to them to be translated back to English. Comparing the source texts with results of their back-rendering, this study was capable of fulfilling the outlined objectives. The results of this study show that (1) the politeness degrees of interpersonal utterances in the source language were generally equivalent to their counterparts in the target language; (2) there was a positive correlation between the English utterances and their back-translations; (3) the politeness degrees of the utterances in both the source texts and their back-translations were perceived to be relatively polite; (4) the politeness degrees of interpersonal utterances in the target language have been maintained by using grammatical features and rhetoric which were more formal than those available in the source texts.